2020
DOI: 10.1257/aer.20181052
|View full text |Cite
|
Sign up to set email alerts
|

Online Privacy and Information Disclosure by Consumers

Abstract: I study the welfare and price implications of consumer privacy. A consumer discloses information to a multiproduct seller, which learns about his preferences, sets prices, and makes product recommendations. Although the consumer benefits from accurate recommendations, the seller may use the information to price discriminate. I show that the seller prefers to commit to not use information for pricing in order to encourage information disclosure. However, this commitment hurts the consumer, who could be better o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(56 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…The working definition of privacy concern in this study is user's risk perception of their own private information during their use of short-form video APP, and privacy protection behavior means the user's response behavior after perceiving the risk of privacy. Since stepping into the Internet era, many scholars have conducted many researches on the privacy of users and drawn many meaningful conclusions (Ichihashi, 2020;Johnson et al, 2020). Chen et al (2017) found that the concern of network privacy has an impact on the privacy protection behavior of users.…”
Section: Privacy Concern and Privacy Protection Behaviormentioning
confidence: 99%
“…The working definition of privacy concern in this study is user's risk perception of their own private information during their use of short-form video APP, and privacy protection behavior means the user's response behavior after perceiving the risk of privacy. Since stepping into the Internet era, many scholars have conducted many researches on the privacy of users and drawn many meaningful conclusions (Ichihashi, 2020;Johnson et al, 2020). Chen et al (2017) found that the concern of network privacy has an impact on the privacy protection behavior of users.…”
Section: Privacy Concern and Privacy Protection Behaviormentioning
confidence: 99%
“…Static models about privacy have been studied in Gradwohl (2018), who analyzes the problem of full implementation when agents prefer to protect their privacy, in Gilboa‐Freedman and Smorodinsky (2018), who axiomatize preferences over privacy and in Bird and Neeman (2020), who study how to regulate what information a firm can use when interacting with a consumer so as to maximize the consumer's welfare 5 . Finally, in the two‐sided market setting, Hidir and Vellodi (2018) and Ichihashi (2019) have considered letting the consumer directly communicate to the seller via cheap talk or Bayesian persuasion. In our model, however, the consumer reveals information about his private type by responding to the seller's mechanism.…”
Section: Related Literaturementioning
confidence: 99%
“…One could think, for example, about situations where information allows producers to help consumers make better choices (Ichihashi, 2019) or where data is used to construct credit ratings that could potentially improve the allocation of credit (Pagano and Jappelli, 1993).…”
Section: Policymentioning
confidence: 99%